A NIST facility for resonant soft x-ray scattering measuring nano-scale soft matter structure at NSLS-II. (10th March 2021) - Gann, Eliot; Crofts, Thomas; Holland, Glenn; Beaucage, Peter; McAfee, Terry; Kline, R Joseph; Collins, Brian A; McNeill, Christopher R; Fischer, Daniel A; DeLongchamp, Dean M
Abstract: We present the design and performance of a polarized resonant soft x-ray scattering (RSoXS) station for soft matter characterization built by the national institute of standards and technology at the national synchrotron light source-II (NSLS-II). The RSoXS station is located within the spectroscopy soft and tender beamline suite at NSLS-II located in Brookhaven national laboratory, New York. Numerous elements of the RSoXS station were designed for optimal performance for measurements on soft matter systems, where it is of critical importance to minimize beam damage and maximize collection efficiency of polarized x-rays. These elements include a novel optical design, sample manipulator and sample environments, as well as detector setups. Finally, we will report the performance of the measurement station, including energy resolution, higher harmonic content and suppression methods, the extent and mitigation of the carbon absorption dip on optics, and the range of polarizations available from the elliptically polarized undulator source.